Elucidating electrochemical intercalation mechanisms of biomass‐derived hard carbon in sodium‐/potassium‐ion batteries. Issue 4 (4th May 2021) - Zhu, Ziyi; Zhong, Wentao; Zhang, Yanjia; Dong, Peng; Sun, Shigang; Zhang, Yingjie; Li, Xue
Abstract: Hard carbon materials are characterized by having rich resources, simple processing technology, and low cost, and they are promising as one of the anode electrodes for commercial applications of sodium‐/potassium‐ion batteries. Simultaneously, exploring the alkali metal ion storage mechanism is particularly important for designing high‐performance electrode materials. However, the structure of hard carbon is more complex, and the description of energy storage behavior is quite controversial. In this study, the Magnolia grandiflora Lima leaf is used as a precursor, combined with simple pyrolysis and impurity removal processes, to obtain biomass‐derived hard carbon material (carbonized Magnolia grandiflora Lima leaf [CMGL]). When it is used as an anode for sodium‐ion batteries, it exhibits a high specific capacity of 315 mAh/g, and the capacity retention rate is 90.0% after 100 cycles. For potassium‐ion batteries, the charge specific capacity is 263.5 mAh/g, with a capacity retention rate of 85.5% at the same cycling. Furthermore, different electrochemical analysis methods and microstructure characterization techniques were used to further elucidate the sodium/potassium storage mechanism of the material. All the results indicate that the high potential slope region represents the adsorption/desorption characteristics on the surface active sites, whereas the low‐potential quasiplateau region belongs to the ion insertion/extraction in the graphitic microcrystallites interlayer. It is noteworthy that potassium ion is randomly intercalated between the graphitic microcrystallite layer without forming a segmented intercalation compound structure. Abstract : To make full use of waste biomass resources, the Magnolia grandiflora Lima leaf is used as a precursor to obtain derived hard carbon material, which showed an excellent electrochemical performance as the sodium‐/potassium‐ion batteries anode, and the different electrochemical analysis methods and microstructure characterization techniques also further explain the corresponding energy storage mechanisms.